2011
DOI: 10.3116/16091833/12/4/171/2011
|View full text |Cite
|
Sign up to set email alerts
|

On the spin-to-orbit momentum conversion operated by electric field in optically active Bi12GeO20 crystals

Abstract: Abstract. An optical conversion of spin angular momentum to orbital angular momentum (SAM-to-OAM) that appears in Bi 12 GeO 20 crystals under the effect of conically shaped external electric field due to a Pockels effect has been studied both experimentally and theoretically. We have revealed the appearance of a doughnut mode and an optical vortex in the system consisting of a right-handed circular polariser, a sample subjected to conical electric field, and a left-handed circular analyser. It has been found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently we have suggested and verified experimentally several methods for the SAM-to-OAM conversion based on piezooptic effect induced in single crystals by torsion or bending [18][19][20]. Besides, electrooptic Pockels effect induced in single crystals by a conically shaped electric field has been found to be a convenient method for SAM-to-OAM converting and operating the efficiency of the vortex beam generation by an electric field applied [21,22]. Let us remind that the Pockels effect can be utilized while controlling electrooptically the entanglement of SAM and OAM [23], thus being applicable for quantum teleportation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently we have suggested and verified experimentally several methods for the SAM-to-OAM conversion based on piezooptic effect induced in single crystals by torsion or bending [18][19][20]. Besides, electrooptic Pockels effect induced in single crystals by a conically shaped electric field has been found to be a convenient method for SAM-to-OAM converting and operating the efficiency of the vortex beam generation by an electric field applied [21,22]. Let us remind that the Pockels effect can be utilized while controlling electrooptically the entanglement of SAM and OAM [23], thus being applicable for quantum teleportation.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, as shown in the study [22], doughnut modes can be generated via the Pockels effect only in the crystals containing three-fold or six-fold inversion axes among their symmetry operations. Let us also remind that all of the methods of vortex beam generation that rely on single crystals can induce single-charged optical vortices only [18][19][20][21][22]. Furthermore, due to symmetry limitations only the bending method of vortex beam generation can be realized for isotropic materials, though even this method cannot be used if the working media are liquid or gaseous.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that twisting of crystals [12,13] or application of conically shaped electric fields to electro-optic crystals [14][15][16] enable the creation of polarization singularities in the beam center if the incident parallel beam has an approximately plane phase front. Moreover, the efficiency of the SAM-to-OAM conversion can be tuned by changing the twisting moment (in the case of a torsion effect in crystals) or the external electric field (when a conically shaped spatial distribution of this field is created in crystals).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have shown [19][20][21] that mechanical torsion of crystals or a conically shaped electric field applied to electro-optic crystals [22][23][24] facilitate creating polarization singularities in the beam center, provided that the incident beam is parallel and has a nearly plane phase front. Moreover, then the efficiency of the SAM-to-OAM conversion can be controlled by changing the twisting moment or the electric field (i.e., the electrical driving signal).…”
Section: Introductionmentioning
confidence: 99%